2014
DOI: 10.1111/liv.12433
|View full text |Cite
|
Sign up to set email alerts
|

Functional hepatocellular regeneration in elderly patients undergoing hepatectomy

Abstract: Our results suggest that functional hepatocellular regeneration is early, fast and similar between elderly and younger patients. Thus, age alone, does not appear to represent an absolute contraindication to hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The growth ratio did not, however, depend on patient age (Supplementary Figure S2). Our results are consistent with previous work [29,30,32,35,36] showing that functional liver regeneration occurs early and rapidly in older and younger patients alike. At the same time, one study [37] found age to correlate inversely with early liver regeneration in patients undergoing major hepatectomy, and those authors concluded that massive blood loss should be avoided to ensure early liver regeneration in older patients [37].…”
Section: Discussionsupporting
confidence: 93%
“…The growth ratio did not, however, depend on patient age (Supplementary Figure S2). Our results are consistent with previous work [29,30,32,35,36] showing that functional liver regeneration occurs early and rapidly in older and younger patients alike. At the same time, one study [37] found age to correlate inversely with early liver regeneration in patients undergoing major hepatectomy, and those authors concluded that massive blood loss should be avoided to ensure early liver regeneration in older patients [37].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that liver regeneration was not affected by age, which is consistent with previously published results [ 7 , 8 , 40 , 41 ]. Although age is a very important consideration when selecting candidates for liver surgery, our study concluded that liver regeneration in older patients was similar to that in younger patients undergoing the same surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Only 8%–15% of patients undergoing hepatic resection are older than 70 years due to the increasing prevalence of comorbidities that confer a high surgical risk. [ 32 ] WT mice aged 15–17 months were treated with either siCtrl or siMCJ, and 24 h later, 70% Phx was performed. The mice were sacrificed 72 h after the procedure.…”
Section: Resultsmentioning
confidence: 99%